Numerical simulation of hydraulic fracture propagation under energy supplement conditions - Dong, Jingfeng; Qu, Hongyan; Zhang, Jingchun; Han, Feipeng; Zhou, Fujian; Shi, Peize; Shi, Jilong; Yu, Tianxi (Frontiers in Earth Science, 2023)
After the long-term production, due to the influence of low-pressure and low-stress fields in the near-well area, the new fractures formed by temporary plugging have a short steering and extension distance, and it is difficult to extend to the high-pressure remaining oil enrichment areas on both sides of the original fractures, resulting in a low increase in the bandwidth of the fracture group after fracturing. The effect of repeated transformation is limited, which affects the degree of reservoir utilization. In the early stage of repeated fracturing, a large amount of pre-fracturing fluid is injected to supplement the energy of the original fracture and rapidly increase the pore pressure in the local range. First, it can weaken rock strength and transform pore structure.Secondly, the combination of pre-pressure energy replenishment and reservoir reconstruction, coupled reconstruction of the seepage field and stress field, promotes the effective expansion of new fractures. In the process of increasing formation energy by energized fracturing, the propagation law of hydraulic fractures and natural fractures is not clear. In this paper, the finite element model of tight sandstone reservoir parameters in the HQ block of Ordos Basin is established by ABAQUS finite element software, combined with the effective stress principle and the theoretical method of fluid-solid coupling numerical simulation. The propagation law of single hydraulic fracture and the interaction state between hydraulic fracture and natural fracture under the condition of energy increase is quantified, and the propagation law of energy storage in the process of energized fracturing is explored, to better guide the field energized fracturing operation. The results show that for every 1MPa increase in a single hydraulic fracture, the length of the hydraulic fracture increases by 0.62m and the maximum fracture width decreases by 0.09mm. When the formation energy is increased by 6MPa, the time for the hydraulic fracture to reach the intersection point with the natural fracture is shortened by 10 %, and the length of the natural fracture is 2.16 times that of the 3MPa. The fracture morphology of 9MPa and 6MPa is similar, so the effect of energy increase is limited.